(untitled) (European Journal of Pure and Applied Mathematics, 2018)
A semigroup is called a GV-inverse semigroup if and only if it is isomorphic to a semilattice of π-groups. In this paper, we give the sufficient and necessary conditions for a GV-inverse semigroup to be a strong semilattice of π-groups. Some conclusions about Clifford semigroups are generalized.